Locating fault using voltage sags profile for underground distribution system - Mokhlis, Hazlie; Li, H.Y.; Bakar, A.H.A.; Mohamad, H. (IEEE, 2010)
This paper presents an alternative fault location algorithm to estimate short-circuit faults location in electrical distribution networks using only voltage sags data. The proposed algorithm uses voltage sags profile as a means to locate fault. The possible fault locations is estimated by incorporating the measured voltage sags magnitude and its corresponding phase angle into an equation of voltage sag as a function of fault distance. A ranking procedure is also introduced to rank possible fault locations due the same electrical distance. The uncertainty of fault resistance is also considered in this algorithm. The performance of the technique is presented by testing it using an actual underground distribution network. The simulation results indicated a possibility of practical implementation.